Process Variation in Liver, Kidney, and Pancreas Transplantation: A Multicenter Evaluation From the Consortium for the Holistic Assessment of Risk in Transplant - Alexandra T. Strauss, MD, PhD, MIE; Juan Carlos Caicedo, MD; Whitney Welsh, PhD; Rhiannon Deierhoi Reed, PhD; Elisa J. Gordon, PhD; David Taber, PharmD; Yue Harn Ng, MD; Katie Ross-Driscoll, PhD; Jesse D. Schold, PhD; Marina Serper, MD; Andrew Olson, MPP; Jessica L. Harding, PhD; et al. (Transplantation Direct)
Background. Transplant center processes for determining candidacy are complex, poorly documented, ambiguous, and variable across centers. Opaque and nonstandardized transplant processes can compromise data collection and lead to inconsistent outcomes. Methods. To understand process variation and data quality in transplantation, we surveyed 8 abdominal transplant centers in an existing research consortium about their processes of care for liver, kidney, and pancreas transplants. We used the Systems Engineering Initiative for Patient Safety model to identify variation related to people, tasks, tools, environment, and processes. Results. Centers varied in their processes across phases of transplant care, including screening referral, waitlist maintenance, and posttransplant follow-up. Regarding referrals, transplant centers chose their locations for outreach to and education for referring providers based on historical density or by request (63%). Additionally, screening of referred patients for transplant evaluation varied across centers related to screening method, screening timing/attempts, and who determines eligibility. For patients declined for listing, only 25% of centers had a formal appeal process (liver only), and most centers had either an informal appeal process (liver: 50%, kidney and pancreas: 87.5%) or none (liver: 25%, kidney and pancreas: 12.5%). Conclusions. In light of increased national attention to improving data collection, processes of care, and workforce efficiency, our findings provide insight into processes that may inform effective transplant practices and identify targets for future interventions.